2006
DOI: 10.1007/s10826-006-9038-9
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Cultural Threads: A Qualitative Study of Culture and Ethnic Identity Among Urban Southwestern American Indian Youth Parents and Elders

Abstract: We utilized qualitative methods to explore ethnic and cultural identity among urban Southwestern American Indian youth, parents, and elders. Twenty-four respondents ranging in age from approximately 13 to 90 years were interviewed in focus groups divided by age. Six major themes and seventeen sub-themes related to tribal and pan-American Indian ethnic identity were identified. Two important findings emerging from our study were that common ethnic identity constructs can be validated and new identity constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…For American Indian families, the family's relationship with elders enhances resiliency (Johnson, 1995). Several focus groups that we conducted with American Indian youths, parents, and elders from reservation and urban settings revealed the critical value of "respect" for elders among American Indians and how this value makes American Indian culture unique from others (House, Stiffman, & Brown, 2006).…”
mentioning
confidence: 96%
“…For American Indian families, the family's relationship with elders enhances resiliency (Johnson, 1995). Several focus groups that we conducted with American Indian youths, parents, and elders from reservation and urban settings revealed the critical value of "respect" for elders among American Indians and how this value makes American Indian culture unique from others (House, Stiffman, & Brown, 2006).…”
mentioning
confidence: 96%
“…For instance, Stiffman et al (2007) Furthermore, this finding in the current study does not suggest that urban AI adolescents are not interested in AI culture or traditions. In fact, in a recent study by House et al (2006) 40% of urban AI adolescents reported that the most important aspects of their AI identity and culture included AI traditions, rituals, and ceremonies while about 46% shared being most proud of the aforementioned. Thus, it seems reasonable that urban AI adolescents value AI traditions and culture but may not be unable to regularly engage in those traditions and customs due to the limitations that exist in urban areas.…”
Section: Results Concerning the Simple Linear Regression Demonstratedmentioning
confidence: 98%
“…Thus, it is possible that for urban AI adolescents, this specific measure of enculturation limited their scores due to limited access to AI cultural events and opportunities found in urban settings. Additionally, researchers are still attempting to figure out how to best describe and assess enculturation, culture, and ethnicity due to the difficulties associated with these constructs (House et al, 2006). This process appears even more difficult when exploring the role of enculturation among urban AI adolescents and warrants further investigation.…”
Section: Results Concerning the Simple Linear Regression Demonstratedmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these factors are inter-related, each having meaning through its association with other factors. Williams (2005) and others (Angell, 2000;Brady, 1995;House, Stiffman, & Brown, 2006;Zimmerman et al, 1996) further suggest that the ability to develop and maintain a bicultural identity is a contributor to well-being. Those who were able to develop clear bi-cultural identities found ways to comfortably fit in their own Aboriginal community and in the dominant Euro-Canadian society, and be successful in achieving their ambitions.…”
mentioning
confidence: 98%